HUBUNGAN FUNGSI AFEKTIF KELUARGA TERHADAP KECERDASAN EMOSIONAL REMAJA DI RT 13 RW 06 KELURAHAN KOTA LAMA MALANG - Yanti Rosdiana; Supri Taba Leki; Tantri Ajeng Purnawati (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2023)
ABSTRACT Adolescence is a period of stressful transition from childhood to adulthood. Adolescents are social beings, the more positive the family function, the better the emotional intelligence of adolescents, and vice versa. The purpose of this study was to determine the affective function of the family on the emotional intelligence of adolescents in Rt 13 Rw 06 Kelurahan Kota Lama Malang. The research used cross sectional design. The population of this study were all adolescents in Kota Lama Malang Sub-District as many as 67 people with a total sample of 47 people. Samples were taken by Simple Random Sampling technique. The independent variable is the affective function of the family, the dependent variable is emotional intelligence. The instrument used is a questionnaire. Data analysis used the fisher's exact test. The results showed that the majority of respondents had family affective function in the good category, most of the respondents had emotional intelligence in the good category and there was a relationship between family affective function and adolescent emotional intelligence in Rt 13 Rw 06 Kelurahan Kota Lama Malang with p = (0.000) . Based on the results of this study, it is hoped that adolescents will be able to control their emotional intelligence properly by listening to their parents and teachers at school. Keywords: Family Affective Function; Emotional Intelligence And Adolescents